Mutational landscape and patterns of clonal evolution in relapsed pediatric acute lymphoblastic leukemia - Waanders, Esmé; Gu, Zhaohui; Dobson, Stephanie M; Antić, Željko; Crawford, Jeremy Chase; Ma, Xiaotu; Edmonson, Michael N; Payne-Turner, Debbie; van de Vorst, Maartje; Jongmans, Marjolijn C J; McGuire, Irina; Zhou, Xin; et al. (Blood cancer discovery, 2020)
Relapse of acute lymphoblastic leukemia (ALL) remains a leading cause of childhood death. Prior studies have shown clonal mutations at relapse often arise from relapse-fated subclones that exist at diagnosis. However, the genomic landscape, evolutionary trajectories and mutational mechanisms driving relapse are incompletely understood. In an analysis of 92 cases of relapsed childhood ALL, incorporating multimodal DNA and RNA sequencing, deep digital mutational tracking and xenografting to formally define clonal structure, we identify 50 significant targets of mutation with distinct patterns of mutational acquisition or enrichment. , and Ras signaling mutations rose from diagnosis subclones, whereas variants in and were exclusively observed at relapse. Evolutionary modeling and xenografting demonstrated that relapse-fated clones were minor (50%), major (27%) or multiclonal (18%) at diagnosis. Putative second leukemias, including those with lineage shift, were shown to most commonly represent relapse from an ancestral clone rather than a truly independent second primary leukemia. A subset of leukemias prone to repeated relapse exhibited hypermutation driven by at least three distinct mutational processes, resulting in heightened neoepitope burden and potential vulnerability to immunotherapy. Finally, relapse-driving sequence mutations were detected prior to relapse using deep digital PCR at levels comparable to orthogonal approaches to monitor levels of measurable residual disease. These results provide a genomic framework to anticipate and circumvent relapse by earlier detection and targeting of relapse-fated clones.